Effects of oxidation cross-linking and sintering additives (TiN, B) on the formation and heat-resistant performance of polymer-derived SiC(Ti, B) films. Issue 7 (15th May 2016) - Xu, Xiaohui; Mao, Yu; Chen, Fen; Yao, Rongqian; Feng, Zude; Chen, Lifu; Zhang, Ying
Abstract: Effects of oxidation cross-linking and sintering additives (TiN, B) on the microstructure formation and heat-resistant performance of freestanding SiC(Ti, B) films synthesized from Ti, B-containing polycarbosilane (TiB-PCS) precursor were investigated. TiB-PCS green films were first cross-linked for 1 h, 2 h, 3 h and 4 h, respectively, and then pre-sintered at 950 °C. Finally, they were sintered at 1800 °C to complete the conversion from organic films to inorganic SiC(Ti, B) films. The results reveal that curing time has a great impact on the uniformity and density of SiC(Ti, B) films. TiB-PCS films cured for 3 h yield the best quality SiC(Ti, B) films, which are composed of β-SiC crystals, C clusters, α-SiC nano-crystals, a small amount of TiB2 and B4 C. TiB2 and B4 C are both steady phases which can inhibit abnormal growth of β-SiC, effectively reduce sintering temperature and help consume excess C from decomposition of amorphous SiO x C y . After high temperature annealing at 1500 °C, 1600 °C and 1700 °C in argon, SiC(Ti, B) films still keep excellent mechanical properties, which makes them attractive candidate materials for microelectromechanical systems (MEMS) used at ultra-high temperatures (exceeding 1500 °C).